English Literature Students’ Pragmatic Knowledge: Analysis of Strategy and Politeness of Refusal - Nuzulia, Rahma; Agustina, Pradipta (SALEE: Study of Applied Linguistics and English Education, 2022)
This study investigates and describes English literature students’ pragmatic knowledge in uttering English refusal statements in different situations (request, invitation, suggestion, offering). The purpose of this study is to analyze and describe students’ refusal strategy and politeness strategy while uttering English refusal. The participants in this study consisted of twenty-five undergraduate students, 7 males and 18 females, enrolled in the second and sixth semesters of the English literature department of Diponegoro University. The only instrument used by researchers in this study was a questionnaire based on Beebe et al.’s (1990) work. The result showed that the students use direct and indirect refusal strategies to refuse something. Most students prefer a direct refusal strategy to the interlocutors who are their peers (friends) or subordinates. However, some students (higher semester) prefer indirect strategies with their peers in some situations. It means that the students respect their interlocutor even though they are in a higher position. Moreover, in the politeness strategy, they use two types of strategies which are deference and solidarity politeness strategy. However, the students (higher semester) prefer to use the deference politeness strategy.